2019
DOI: 10.29392/joghr.3.e2019032
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal care in Rwanda: facilitators and barriers to postnatal care attendance and recommendations to improve participation

Abstract: Back Background ground Sub-Saharan Africa has the highest rates of neonatal mortality in the world with an estimated 1.2 million deaths within the first 28 days of life. Postnatal care (PNC) can contribute to reductions in morbidity and mortality in mothers and newborns through vital support that identifies danger signs and establishes valuable practices and referral processes. Methods Methods This qualitative data was collected as a part the East Africa Preterm Birth Initiative (PTBi-EA) to guide development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…38 The CHW infrastructure is valued and well‐accepted, but engaging CHWs to provide care for women after cesarean deliveries requires additional training and tools to deliver unified messages on topics specific to cesarean birth, such as wound hygiene, rest, physical activity, and mental health. 8 , 10 Further research on how to best integrate these instructions within CHW home visits is being explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 The CHW infrastructure is valued and well‐accepted, but engaging CHWs to provide care for women after cesarean deliveries requires additional training and tools to deliver unified messages on topics specific to cesarean birth, such as wound hygiene, rest, physical activity, and mental health. 8 , 10 Further research on how to best integrate these instructions within CHW home visits is being explored.…”
Section: Discussionmentioning
confidence: 99%
“… 8 Across several studies, women delivering via cesarean in Rwanda reported a lack of instructions or conflicting instructions at the time of discharge. 8 , 9 , 10 A scoping review found that very few studies based in SSA comment on cesarean recovery activities or postoperative care pathways after hospital discharge, and even fewer studies provide concrete recommendations. 11 Here, we outline recommendations for discharge instructions to be provided to women who have given birth by cesarean in SSA to optimize their recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Other factors were related to the health system such as insufficient staff, poor reception of clients, lack of trust and confidentiality between clients and health care providers, lack of sensitization and information, and midwives' workloads [41]. In addition, patient-centered care practices, capacities to conduct postnatal information, education, and counseling are considered among the main barriers to the use of proper postnatal care mainly in remote areas of low-and middle-income nations [39,42].…”
Section: Barriersmentioning
confidence: 99%
“…The World Health Organization guidelines addressing postpartum care are welldefined and able to apply and accommodate such communities with low resources [41]. These interventions often complement and enhance the role played by services such as health promotion and education for health care services like family planning, antenatal care, delivery in a skilled birth attendant, and postnatal care [25,42]. Social and behavior change interventions are critical to ensure that populations that are most in need can access available services and products.…”
Section: Advocate For Best Practices In the Postpartum Periodmentioning
confidence: 99%